The Psychological Skill Level of Bengkulu Athletes During the Covid-19 Pandemic - Yahya Eko Nopiyanto; Septian Raibowo; Novriansyah Novriansyah; Fitri Agung Nanda (STKIP Muhammadiyah Kuningan, 2021)
The Covid-19 pandemic has had a tremendous impact on sporting events. This research aimed to determine the psychological skill level of Bengkulu PON athletes during the Covid-19 pandemic. The research method used in this study was a quantitative descriptive method with a survey approach. The subjects of this research were all athletes of PON Bengkulu, with a total of 83 athletes. The data of the research variable was collected using a questionnaire,